12-Week, Single-Center Study of a Targeted Pigment-Correcting Dark Spot Treatment for Post-Inflammatory Hyperpigmentation and Solar Lentigines - Makino ET; Huang P; Cheng T; Acevedo SF; de Oliveira C; Mehta RC (Dove Medical Press, 2023)
Elizabeth T Makino,1 Priscilla Huang,1 Tsing Cheng,1 Summer F Acevedo,2 Cristiane de Oliveira,2 Rahul C Mehta1 1SkinMedica - Allergan Aesthetics, an AbbVie Company, Irvine, CA, USA; 2SGS Stephens Inc, Richardson, TX, USACorrespondence: Elizabeth T Makino, Clinical Development, Skincare, Allergan Aesthetics, an AbbVie Company, 2525 DuPont Drive, Irvine, CA, 92612, USA, Email elizabeth.makino@abbvie.comPurpose: Post-inflammatory hyperpigmentation (PIH) and solar lentigines are dark spots of skin from excessive melanin production due to injury or UV exposure. This 12-week single-center study assessed the efficacy and tolerability of a novel targeted pigment-correcting spot treatment gel suspension cream (Dark Spot Treatment) for improving mild-to-moderate PIH or solar lentigines.Patients and Methods: Female participants (N = 41) aged 25- 65 with mild-to-moderate facial dark spots applied Dark Spot Treatment daily for 12 weeks. Investigators assessed overall hyperpigmentation, skin tone evenness, and dark spot intensity, contrast, and size at Weeks 2, 4, 8, and 12. Participant self-assessments occurred at Weeks 1, 2, 4, 8, and 12. Tolerability was assessed by clinical grading and participant reporting.Results: Dark Spot Treatment improved overall hyperpigmentation, skin tone evenness, and dark spot intensity and contrast at Weeks 2 through 12, and dark spot size at Weeks 4 through 12 (all p < 0.001 compared to baseline). Participant self-assessments showed high overall satisfaction. Dark Spot Treatment was well tolerated.Conclusion: The novel pigment-correcting Dark Spot Treatment significantly improved the appearance of PIH and solar lentigines, had high participant satisfaction, and was well tolerated.Keywords: post-inflammatory hyperpigmentation, age spots, solar lentigines, Dark Spot Treatment